Clonal Expansion of Hepatic Stem/Progenitor Cells following Flow Cytometric Cell Sorting - Atsushi Suzuki (Cell Transplantation, 2001)
Although hepatic stem cells are believed to exist and play a critical role in developing and regenerating liver, little is known about their cell surface specificity or differentiation capabilities. To make prospective studies of hepatic stem cells possible, we established an in vitro culture system for identification and characterization of hepatic stem/progenitor cells. By combining this culture system with fluorescence activated cell sorting (FACS), a population of cells that were capable of forming large colonies and providing their descendants for relative longer period was isolated from fetal mouse livers. These data suggest that hepatic stem/progenitor cells with high proliferative potential are existent in the developing mouse liver, and that they are enriched by using flow cytometry.